Transsphenoidal pituitary surgery in the elderly is safe and effective. (October 2014) - Pereira, Erlick A. C.; Plaha, Puneet; Chari, Aswin; Paranathala, Menaka; Haslam, Nicholas; Rogers, Angela; Korevaar, Tim; Tran, Diane; Olarinde, Remi; Karavitaki, Niki; Grossman, Ashley B.; Cudlip, Simon A.
Abstract Object. With an increasingly ageing population, the number of elderly people diagnosed with pituitary tumours continues to rise. There is a concern that with increasing age and comorbidities, there is higher anaesthetic risk, as well as peri-operative morbidity and mortality from pituitary surgery. This study aimed to audit the benefits and complications of transsphenoidal surgery performed in a large pituitary centre in elderly patients. Methods. Data on all elderly patients (age: ≥ 70 years) undergoing transsphenoidal surgery at a large tertiary referral centre between November 2003 and August 2012 were collected retrospectively. Results. A total of 104 operations were performed on 102 patients during 106 months. Median age was 75.2 years (range: 70–94) and 63 (61%) of the patients were male. Median follow-up was 15.2 months (range: 2.3–84.4). The majority presented with either peripheral visual field defects (26.4%) or pituitary hormone deficits (17.9%). A significant number (21.7%) of tumours were incidental radiological findings while investigating other diagnoses like stroke and dementia. 48.1% of operations were undertaken microscopically and the remaining 51.9% were endoscopic. Median hospital stay was 4 days (range: 3–18). Intra-operative complications included hypotension (1.9%) and blood loss requiring transfusion (2.9%). The 30-day complications included transient diabetes insipidus (9.6%), syndrome of inappropriate anti-diuretic hormone secretion (8.7%), delayed cerebrospinal fluid leak requiring lumbar drainage (0.9%) with no patient requiring formal repair. There were no peri-operative deaths. Long-term assessment suggested 79% had improved or stable endocrine function with 7% achieving biochemical cure and 91% showed improved or stable visual fields. Conclusions. Pituitary surgery in the elderly, whether microscopic or endoscopic, has low morbidity and mortality and is a safe and effective intervention for both symptom control and functional outcomes.